(untitled) (Fiep Bulletin - online, 2013)
The absence of good physical fitness to health is strongly associated to hypokinetic deseases predisposition, most of the times resulting in deaths. Considering that physical activity can exert great influence on health, this study aimed at evaluating the efects of a multidisciplinary intervention program in the level of health-related physical fitness (HRPF) of well-nourished children with overweight risk, with overweight and obese. The sample was composed of 11 well-nourished overweight risk children, 14 with overweight and 6 obese. The HRPF was evaluated through measurements of Body Mass Index (BMI), flexibility and abdominal strenght/resistance, classifying the results in “below”. “in” and “above” the Body Mass Healthy Zone (BMHZ) and Physical Fitness Healthy Zone (PFHZ). The results show that after the intervention period three children presented improvements in BMI and five in flexibility. However, when Ratio test was applied, data showed that the differences are not statisticaly significant. In conclusion, although improvements have occurred, the program was not enough to cause statisticaly significant changes in HRPF.